SUMBANGAN 'ALI BIN ABI TALIB R.'A DALAM BIDANG 'ULUM AL-NAQLIYYAH - Yusof, Abdullah (Journal of Al-Tamaddun, 2007)
This article will present the contribution made by the fourth Caliph in the Caliph al-Rasyidin?s series which is ?Ali b. Abi Talib in the field of ?Ulum Al-Naqliyyah. Among the important sub-areas are al-Quran and Interpretation, Tauhid, Fiqh, Tilawah al-Quran and others. As a person who lives during the time of the Prophet until his death, his knowledge is unbeatable and is still expanding until now. He is also respected by both Muslim and non-Muslim scholars.